Survival and Integration of Transplanted Olfactory Ensheathing Cells are Crucial for Spinal Cord Injury Repair: Insights from the Last 10 Years of Animal Model Studies - Ronak Reshamwala; Megha Shah; James St John; Jenny Ekberg (Cell Transplantation, 2019)
Olfactory ensheathing cells (OECs), the glial cells of the primary olfactory nervous system, support the natural regeneration of the olfactory nerve that occurs throughout life. OECs thus exhibit unique properties supporting neuronal survival and growth. Transplantation of OECs is emerging as a promising treatment for spinal cord injury; however, outcomes in both animals and humans are variable and the method needs improvement and standardization. A major reason for the discrepancy in functional outcomes is the variability in survival and integration of the transplanted cells, key factors for successful spinal cord regeneration. Here, we review the outcomes of OEC transplantation in rodent models over the last 10 years, with a focus on survival and integration of the transplanted cells. We identify the key factors influencing OEC survival: injury type, source of transplanted cells, co-transplantation with other cell types, number and concentration of cells, method of delivery, and time of transplantation after the injury. We found that two key issues are hampering optimization and standardization of OEC transplantation: lack of (1) reliable methods for identifying transplanted cells, and (2) three-dimensional systems for OEC delivery. To develop OEC transplantation as a successful and standardized therapy for spinal cord injury, we must address these issues and increase our understanding of the complex parameters influencing OEC survival.